Investigation of Well Cement Degradation by Carbonated Brine in Supercritical CO2 Environment - Sonny, Sonny Irawan (2010)
Well cement tends to degrade when exposed to carbonated brine. This study focuses on the chemical alteration of cement by carbonated brine in supercritical condition and to estimate the degradation rate of cement by carbonated brine attack by using Fick’s Law and Elovich equation. Correlation between temperature, pressure, concentration and pH towards degradation depth of cement was investigated. Class G cement (w/c = 0.44) was used as it is widely used in oil and gas well construction and prepared according to API recommended practice 10B-2 by using constant speed mixer. Curing of cement slurry and CO2 exposure test were done by using curing chamber and High Pressure and High Pressure Vessel (HPHT). It was observed that depth of cement degradation was directly proportional to pressure and concentration but inversely proportional to temperature and pH. The degradation depth of using pure water was about 10 times greater than using brine solution. For a good quality of cement, rate of cement degradation was possibly followed Elovich equation